Single-Walled Carbon Nanohorns Decorated with Silver Nanostructures as an Enhanced Voltammetric Platform for Nitrate Monitoring - Pizarro-Konczak, J; Aguirre-Quintana, M; Aguirre-Quintana, M; Segura-Segura, R; Segura-Segura, R; Paz de la Vega-Quiroz, A; Paz de la Vega-Quiroz, A; Liendo-Ibarra, F; Liendo-Ibarra, F; Penagos-Llanos, J; Penagos-Llanos, J (Elsevier Ltd, 2025)
Accurate and selective detection of nitrate is essential due to the environmental and health risks posed by excessive nitrate levels in water supplies. In this work, a novel electrochemical sensor for nitrate detection is presented, based on a glassy carbon electrode (GCE) modified with single-walled carbon nanohorns (SWCNHs) and electrochemically synthesized silver nanostructures (AgNSs). The combination of SWCNHs and AgNSs (AgNSs/SWCNHs/GCE) enhances the electrochemically active surface area (ECSA) of the sensor compared to AgNSs/GCE, resulting in superior sensitivity for nitrate analysis. The performance of the sensor was evaluated by square wave voltammetry (SWV) and characterized by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and cyclic voltammetry (CV). Under optimized conditions: 2.0 μL of 1.0 mg mL-1 SWCNHs on the GCE and a 2-second electrodeposition of AgNSs at -0.8 V vs. saturated calomel electrode (SCE), the sensor exhibited a linear response to nitrate concentrations ranging from 0.2 to 100.0 mg L-1, with a detection limit of 0.17 mg L-1. The sensor demonstrated excellent repeatability, reproducibility, strong anti-interference with common ions (NO₂⁻, NH₄⁺, Cl⁻, ClO₄⁻, Mg²⁺, K⁺, Na⁺), and was successfully applied to nitrate detection in tap water, showing consistent and reliable results. This study highlights the potential of the developed sensor for environmental monitoring and water quality analysis. © 2025